Virus-Derived DNA Forms Mediate the Persistent Infection of Tick Cells by Hazara Virus and Crimean-Congo Hemorrhagic Fever Virus - Salvati, Maria Vittoria; Salaris, Claudio; Monteil, Vanessa; Del Vecchio, Claudia; Palù, Giorgio; Parolin, Cristina; Calistri, Arianna; Bell-Sakyi, Lesley; Mirazimi, Ali; Salata, Cristiano (Journal of virology, 2021)
Crimean-Congo hemorrhagic fever (CCHF) is an emerging tick-borne viral disease caused by CCHF virus (CCHFV). Ticks of the genus Hyalomma can be persistently infected with CCHFV representing the viral reservoir, and the main vector for viral transmission. Crimean-Congo hemorrhagic fever (CCHF) is a severe disease of humans caused by CCHF virus (CCHFV), a biosafety level (BSL)-4 pathogen. Ticks of the genus Hyalomma are the viral reservoir, and they represent the main vector transmitting the virus to its hosts during blood feeding. We have previously shown that CCHFV can persistently infect Hyalomma -derived tick cell lines. However, the mechanism allowing the establishment of persistent viral infections in ticks is still unknown. Hazara virus (HAZV) can be used as a BSL-2 model virus instead of CCHFV to study virus/vector interactions. To investigate the mechanism behind the establishment of a persistent infection, we developed an in vitro model with Hyalomma -derived tick cell lines and HAZV. As expected, HAZV, like CCHFV, persistently infects tick cells without any sign of cytopathic effect, and the infected cells can be cultured for more than 3 years. Most interestingly, we demonstrated the presence of short viral-derived DNA forms (vDNAs) after HAZV infection. Furthermore, we demonstrated that the antiretroviral drug azidothymine triphosphate could inhibit the production of vDNAs, suggesting that vDNAs are produced by an endogenous retrotranscriptase activity in tick cells. Moreover, we collected evidence that vDNAs are continuously synthesized, thereby downregulating viral replication to promote cell survival. Finally, vDNAs were also detected in CCHFV-infected tick cells. In conclusion, vDNA synthesis might represent a strategy to control the replication of RNA viruses in ticks allowing their persistent infection. IMPORTANCE Crimean-Congo hemorrhagic fever (CCHF) is an emerging tick-borne viral disease caused by CCHF virus (CCHFV). Ticks of the genus Hyalomma can be persistently infected with CCHFV representing the viral reservoir, and the main vector for viral transmission. Here we showed that tick cells infected with Hazara virus, a nonpathogenic model virus closely related to CCHFV, contained short viral-derived DNA forms (vDNAs) produced by endogenous retrotranscriptase activity. vDNAs are transitory molecules requiring viral RNA replication for their continuous synthesis. Interestingly, vDNA synthesis seemed to be correlated with downregulation of viral replication and promotion of tick cell viability. We also detected vDNAs in CCHFV-infected tick cells suggesting that they could represent a key element in the cell response to nairovirus infection and might represent a more general mechanism of innate immunity against RNA viral infection.